The Effects of Length of Residence and Exposure to Violence on Perceptions of Neighborhood Safety in an Urban Sample. - Guo, Monica; O'Connor Duffany, Kathleen; Shebl, Fatma M; Santilli, Alycia; Keene, Danya E (Journal of Urban Health, 2018)
Perceptions of neighborhood safety shape the well-being of individuals and communities, affecting neighborhood walkability, associated physical activity behaviors, and health conditions. However, less is known about the factors that determine perceptions of safety. One factor that may affect perceptions of neighborhood safety is the length of time someone has lived in their neighborhood. We use a representative, adult sample of urban low-income residents from the 2015 New Haven Health Survey (n = 1189) to investigate the associations between length of residence (new residents of < 1 year in neighborhood versus longer-term residents of 1 or more years in neighborhood) and perceptions of neighborhood safety (whether feeling unsafe to walk at night). We then examine the potential moderating effect of exposure to neighborhood violence on these associations. We find that the association between length of residence and perceived safety differs by exposure to neighborhood violence. Among those unexposed to neighborhood violence, longer-term neighborhood residents were more likely to feel unsafe compared to new residents (OR = 2.03, 95% CI 1.19, 3.45). Additionally, the effect of exposure to violence on feelings of safety was larger for new residents (OR = 9.10, 95% CI 2.72, 30.44) compared to longer-term residents (OR = 1.88, 95% CI 1.28, 2.77). Our findings suggest that length of residence may have implications for feelings of safety, and that experiences of violence may uniquely contribute to feelings of unsafety among new residents. These findings hold implications for interventions and policy efforts aimed at neighborhood safety improvements through community development, housing, or city urban planning initiatives, particularly for new neighborhood residents or those who experience neighborhood violence.
Keywords: *Exposure to Violence/px [Psychology]; *Exposure to Violence/sn [Statistics & Numerical Data]; *Poverty/px [Psychology]; *Poverty/sn [Statistics & Numerical Data]; *Residence Characteristics/sn [Statistics & Numerical Data]; *Safety/sn [Statistics & Numerical Data]; *Urban Population/sn [Statistics & Numerical Data]; Adult; Age Factors; Aged; Exposure to Violence; Exposure to violence; Female; Humans; Length of residence; Male; Middle Aged; Neighborhood; Perceptions of safety; Poverty; Residence Characteristics; Residential stability; Safety; Urban Population; Violence; Young Adult; adult; age; aged; demography; dept.pch; exposure to violence; female; human; male; middle aged; peer-reviewed; poverty; psychology; safety; urban population; young adult

Availability, accessibility, utilization: n-depth interviews with food insecure residents and emergency food providers in new haven, CT - Carroll, Grace; Keene, Danya; Santilli, Alycia; Johannes, Joy; Ickovics, Jeannette; Duffany, Kathleen O’Connor (Journal of Hunger & Environmental Nutrition, 2019)
Approximately 34% of residents from New Haven’s six lowest-income neighborhoods are food insecure, significantly higher than the rest of Connecticut and country (both approximately 12%). To understand the availability, accessibility, and utility of emergency food programs, we conducted 34 semi-structured qualitative interviews with 20 food insecure residents and 14 emergency food providers. Many depend on food programs as a long-term strategy of supplementing groceries rather than a temporary solution in emergency situations; providers are struggling to meet this demand. Transportation and time are barriers to accessing food from programs. Policies and food programs should focus on disseminating accurate information, streamlining policies and practices, and supporting and expanding food programs to meet population need.
Keywords: Food insecurity; adult; article; community health; community-based participatory research; dept.pch; emergency; emergency food programs; food insecurity; food pantries; human; interview; participatory research; peer-reviewed; public health; resident; soup kitchen; soup kitchens

Bridging the response to mass shootings and urban violence: exposure to violence in New Haven, Connecticut - Santilli, Alycia; Duffany, Kathleen O'Connor; Carroll-Scott, Amy; Thomas, Jordan; Greene, Ann; Arora, Anita; Agnoli, Alicia; Gan, Geliang; Ickovics, Jeannette (American Journal of Public Health, 2017)
We have described self-reported exposure to gun violence in an urban community of color to inform the movement toward a public health approach to gun violence prevention. The Community Alliance for Research and Engagement at Yale School of Public Health conducted community health needs assessments to document chronic disease prevalence and risk, including exposure to gun violence. We conducted surveys with residents in six low-income neighborhoods in New Haven, Connecticut, using a neighborhood-stratified, population-based sample (n=1189; weighted sample to represent the neighborhoods, n = 29 675). Exposure to violence is pervasive in these neighborhoods: 73% heard gunshots; many had family members or close friends hurt (29%)or killed (18%)by violent acts. Although all respondents live in low-income neighborhoods, exposure to violence differs by race/ ethnicity and social class. Residents of color experienced significantly more violence than did White residents, with a particularly disparate increase among young Black men aged 18 to 34 years. While not ignoring societal costs of horrific mass shootings, we must be clear that a public health approach to gun violence prevention means focusingonthedualepidemicofmass shootings and urban violence.
Keywords: Adolescent; Adult; African American; African Americans; Aged; Caucasian; Connecticut; European Continental Ancestry Group; Exposure to Violence; Female; Humans; Male; Mass Casualty Incidents; Middle Aged; Poverty Areas; Prevalence; Risk Factors; Self Report; Surveys and Questionnaires; Urban Population; Wounds, Gunshot; adolescent; adult; aged; dept.pch; ethnology; exposure to violence; female; gunshot injury; human; male; mass disaster; middle aged; poverty; prevalence; questionnaire; risk factor; self report; statistics and numerical data; urban population